The dependent, independent and interdependent functions of the nurse practitioner - a legal and ethical perspective - C. Searle (AOSIS, 1982)
In general, contemporary nursing literature from Western countries does not take a bold stand on the very controversial issue of the dependent and independent functions of the nurse practitioner. The authors write as if they are skating on very thin ice. Text books on nursing imply a great deal about the practice potential of nurses but ever and anon there is a subtle reversion to the concept that nursing has certain dependent functions, meaning functions that require a doctor's authorisation, and certain independent functions that are carried out on the nurse's own initiative, and responsibility. In general the majority of authors consulted appear to subscribe to the concept postulated by Sarney when he says A good nursing practice act will separate the independent functions (what nurse can do on her own) from the dependent functions (what she can do only under the direction o f a doctor) (Sarney 1968 : 18).